Population dynamic and pheromone use for early monitoring of Spodoptera exigua Hübner (Lepidoptera: Noctuidae) in Indonesia - Witjaksono, Witjaksono; Trisyono, Y. Andi; Tanjung, Heru Rezki; Azzahra, Zulfa (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Beet armyworm (Spodoptera exigua) poses a challenge for shallot production because it can exist in fields throughout the year. This study aims to observe the dynamic population during shallot off and on-seasons. Additionally, this study aims to determine the correlation between S. exigua moth captures and damage intensity. The research was conducted from November to May in Kretek Village, Parangtritis District, Bantul Regency, Special Region of Yogyakarta Province, Indonesia. Population dynamic observations of S. exigua during the off-season and on-season were conducted in a 100 x 100 m plot with ten pheromone traps installed. The early monitoring study consisted of two treatments: installed pheromone and control (without the installation of pheromones). The plots were separated by approximately 500 m and were approximately 3500 m2 in size. The results showed that S. exigua exists and can survive during shallot off-season and on-season planting periods. The number of male S. exigua moths captured during the on-season was higher compared to the off-season. The fluctuation of rainfall and the number of S. exigua during the off and on-seasons were also observed, showing that rainfall significantly affected the number of S. exigua moths captured. However, the relationship between rainfall and S. exigua population needs further study. Strong positive correlations between population and damage intensity in pheromone-treated fields between three to seven days after observation (DAO) demonstrated that pheromone traps can be used as a monitoring tool for S. exigua. The close correlation between the S. exigua captured and the intensity of the damage that will occur can be prevented by controlling them by farmers.